Improving Futsal Learning Outcomes through TaRL Based on Small-Sided Games - Andika Ihsan Maulana; Yudy Hendrayana; Reshandi Nugraha (Universitas Negeri Semarang, 2026)
Futsal learning in schools is often hampered by students’ low mastery of basic techniques and the wide variation in individual skill levels. This study aims to enhance learning outcomes by integrating the Teaching at the Right Level (TaRL) approach with Small-Sided Games (SSG). Classroom Action Research was conducted in two cycles involving 36 grade XI students. Data were collected using the Game Performance Assessment Instrument, observation sheets, and documentation, then analyzed through descriptive statistics, the Shapiro–Wilk normality test, paired sample t-test, effect size calculations, and percentage of learning completeness. The findings indicated a substantial improvement in student performance, with the average score increasing from 63.31 in the first cycle to 77.72 in the second cycle. The paired sample t-test confirmed a statistically significant increase (p < 0.001). Moreover, the effect size values, ranging from large (d = 1.91) to very large (d = 3.39), demonstrate the strong impact of the intervention. Learning completeness also rose markedly from 13.89% to 86.11%. These results affirm that combining TaRL with SSG is an effective instructional strategy to address ability gaps and improve futsal learning outcomes in school settings.